A quadrature‐hybrid‐integrated reconfigurable feeding network for wideband quad‐polarization‐agile antenna design. Issue 6 (30th March 2021) - Wang, Shi Tong; Sun, Sheng; Sun, Hucheng; Yang, Shiwen; Hu, Jun
Abstract: In this article, a reconfigurable antenna with quad‐polarization radiations is proposed based on a switchable feeding network. A wideband quad‐mode feeding network is first designed by integrating a simple impedance converter with a modified hybrid coupler. By switching the p‐i‐n diodes, four‐transmission status with specific amplitudes and phase differences at feeding output ports can be obtained over a wide frequency range, hence enhancing the radiating bandwidth of two linear and two circular polarizations. Finally, a prototype of the proposed quad‐polarization‐agile reconfigurable antenna is designed and fabricated. The measured results show a wide overlapped bandwidth of 782 to 1010 MHz (25.4%) for all four polarizations with a competitive size and gain performance.